A fast and highly efficient one-pot synthesis of novel isoxazolyl pyrido[2, 3-b][1, 4]oxazin-2(3H)-ones via Smiles rearrangement using task-specific ionic liquid [HMIm]BF4 as green solvent. Issue 1 (2nd January 2017) - Reddy, Modugu Nagi; Kumar, Pittala Praveen; Rajanarendar, Eligeti
ABSTRACT: A facile and convenient procedure for the synthesis of isoxazolyl pyrido[2, 3- b ][1, 4]oxazin-2(3 H )-ones via Smiles rearrangement from isoxazole amine, chloroacetyl chloride and 2-chloro-3-hydroxypyridine using [HMIm]BF4 as task-specific ionic liquid has been described. The protocol proves to be efficient and environmentally benign in terms of high yields, eco-friendly solvent, ease of recovery, and reusability of reaction medium. GRAPHICAL ABSTRACT: